Transition programs for children and youth with diverse needs - Scorgie, Kate; Forlin, Chris (International perspectives on inclusive education ;, 2022)
Volume 18 of International Perspectives on Inclusive Education offers multiple international perspectives on transitions for children and youth with diverse backgrounds and special needs. Transition approaches are viewed from early childhood through to post-secondary and into workplace settings using a unique convergence of integrating research and practice in schools, workplaces, organizations, and communities. Effective evidence-based programs, interventions, and strategies are also incorporated throughout, with a strong emphasis on collaborative partnerships underpinning all aspects of transition. This research is predicated on the assumption that inclusion in academic, social, vocational, and other contexts incorporates all stakeholders. Providing a focus on meaningful involvement and participation in communities and activities of choice, that secure benefits for all, the chapter authors examine both innovative evidence-based practices that facilitate transition, and potential barriers, supplemented by informative case studies. In addition to providing knowledge and skill training for establishing effective transitions, this volume views programs, attitudes, expectations, and perceptions, in relation to what it means to be accorded welcome into a particular setting.